2020
DOI: 10.1017/ice.2020.1262
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of infection control measures to prevent healthcare-associated transmission of severe acute respiratory coronavirus virus 2 (SARS-CoV-2)

Abstract: Care of SARS-CoV-2-positive patients in healthcare institutions is challenging because of potential risk of transmission to other vulnerable patients. We describe infection control measures which were associated with no instances of hospital transmission. Adoption of the infection control bundle described may be helpful to prevent SARS-CoV-2 spread within healthcare institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Our results suggest that the infection control measures and PPE in place at the institution where we conducted this case series 13 can protect against symptomatic SARS-CoV-2 infection, even in settings where the density of individuals infected with SARS-CoV-2 is relatively high. This provides some confidence that PPE and similar infection control measures, when used consistently and correctly, will provide adequate protection in other congregate settings, like schools.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Our results suggest that the infection control measures and PPE in place at the institution where we conducted this case series 13 can protect against symptomatic SARS-CoV-2 infection, even in settings where the density of individuals infected with SARS-CoV-2 is relatively high. This provides some confidence that PPE and similar infection control measures, when used consistently and correctly, will provide adequate protection in other congregate settings, like schools.…”
Section: Discussionmentioning
confidence: 82%
“…The center where we conducted this case series implemented a number of changes to their institutional infection control guidelines based on these sequencing results 13 . The recommendations for extended reuse of medical grade face masks were clarified and now instruct HCP to consider barrier mask replacement after three days of wear, to inspect the barrier mask prior to each use and to replace if soiled or damaged, and to always ask for PPE when needed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To prevent in-hospital outbreaks, contact and airborne precautions have been implemented for patients with COVID-19 with demonstrated success in preventing severe acute respiratory coronavirus virus 2 (SARS-CoV-2) transmission. 1 Data on the rates of secondary infections in patients hospitalized with COVID-19 are limited. 2 Although early studies showed low rates of secondary infections in patients with COVID-19, 3 more recent studies in both larger and sicker populations have shown elevated rates of secondary infection.…”
mentioning
confidence: 99%